Integrative analysis of long non-coding RNAs and mRNAs associated with tumorigenesis of salivary gland pleomorphic adenoma. (January 2022) - Shen, Shukun; Lu, Hao; Liu, Shengwen; Yang, Wenjun; Liu, Limin; Xu, Wanlin
Abstract: Objective: The current study investigated long non-coding RNA (lncRNA) and mRNA profiles of the human salivary gland pleomorphic adenoma (SGPA). Design: Microarray analysis was used to study the expression of lncRNAs and mRNAs and the differentially expressed lncRNAs in human SGPA (all from parotid gland) were identified. The differentially expressed lncRNAs were subjected to qRT-PCR to verify and quantify their expression and a lncRNA-mRNA co-expression network was constructed. The lncRNAs correlated to pleomorphic adenoma gene 1 ( PLAG1 ), a known key transcription factor, were identified and analyzed. Results: In the present study, 17, 382 lncRNAs and 8132 mRNAs were found to be significantly differentially expressed in SGPA (fold change > 2, P < 0.05). The expression of three lncRNAs ( NR_110874, NR_110875 and T087085 ) was significantly altered in SGPA compared to the corresponding healthy tissues, and it was confirmed using the lncRNA-mRNA co-expression network analysis that several lncRNAs interact with 5 key regulators ( PLAG1, CTNNB1, CCND1, IGF2, and TP53 ). Furthermore, T042819 was significantly upregulated in SGPA, which may upregulate PLAG1 by sponging has-miR195–5p. Conclusion: These data suggested that the differently expressed lncRNAs may contribute to the tumorigenesis of SGPA, and analyzing the differences in the lncRNA expression profiles may provide novel insights into the pathogenesis of SGPA. Highlights: The lncRNAs and mRNAs expression was evaluated in SGPA. Certain lncRNAs and mRNAs showed remarkable changes. LncRNA-T042819 may regulate PLAG1 through sponging miR195-5p in SGPA.